SILVER NANOPARTICLES FOR ENHANCEMENT OF ACCUMULATION OF CAPSAICIN IN SUSPENSION CULTURE OF CAPSICUM SP. - Bhat, Pooja; Bhat, Akash (Journal of Experimental Sciences, 2016)
Secondary metabolites can be very important chemicals for the development of plants. The secondary metabolite in this study is obtained from capsicum. Capsaicin is industrially very important due to its wide use range. Thestudy involved is the use of silver nanoparticles for elicitation of levels of capsaicin. Mediums with different hormonal combinations were prepared and growth was studied using qualitative analysis using iodine fumes, Gibbs Reagent and quantitative analysisusing Phosphomolybdic Acid Method and Folin- Ciocalteu method. This brings down a conclusion that the nanoparticles acted as an elicitor and brought about capsaicin increase effectively. Extraction of the metabolite from these natural sources also prove easier and the product can be obtained in a much purified form.